Trazodone and mirtazapine: A possible opioid involvement in their use (at low dose) for sleep?. (March 2020) - Schreiber, S.; Pick, C.G.
Abstract: The efficacy of each antidepressant available has been found equal to that of amitriptyline in double-blind studies. However, a few of them are being prescribed (at under-therapeutic doses) for sleep, in non-depressed persons, when there are relative contraindications for sedative-hypnotics. Following previous studies regarding the antinociceptive mechanisms of various antidepressants, we suggest that the involvement of the opioid system in some of the antidepressants' mechanism of action may contribute to these medications' use for the induction and maintenance of sleep. The mostly prescribed antidepressants for sleep are trazodone (a weak, but specific inhibitor of the synaptosomal uptake of serotonin, that also binds to alpha-1 and alpha-2 adrenoreceptor sites) and mirtazapine (a postsynaptic drug which enhances noradrenergic and 5-HT1A-mediated serotonergic neurotransmission via antagonism of central alpha-2-auto- and hetero-adrenoreceptors). In our previous studies when ICR mice were tested with a hotplate analgesia meter, both trazodone and mirtazapine induced, a naloxone-reversible antinociceptive effect following i.p administration. Summing up the various interactions of trazodone and mirtazapine with opioid, noradrenergic and serotonergic agonists and antagonists, we found that the antinociceptive effect of trazodone is influenced by the opioid receptor subtypes mu and delta (and a clear 5-HT mechanism of antinociception), while the antinociceptive effect of mirtazapine is mainly influenced by kappa and mu opioid receptor subtype (combined with both serotonergic and noradrenergic receptors). This opioid profile of the two drugs may be one of the explanations to their efficacy in the treatment of insomnia, when sedatives (either benzodiazepines or the non-benzodiazepine "Z-compounds") cannot be prescribed.